UD Factorization Based Non-Traditional Attitude Estimation of Nanosatellite with Rate Gyros FDI - Cilden-Guler, Demet; Hajiyev, Chingiz (Elsevier BV, 2018)
Abstract An attitude and rate estimation method with nontraditional approach is presented for the nanosatellite having magnetometer, sun sensor and rate gyros. The approach is based on the singular value decomposition (SVD) aided extended Kalman filter (EKF). Here, EKF uses the measurements after the SVD stage as it provides linear measurements of the attitude angles and their error covariance. In this stage, measurement error covariance matrix is factorized and the measurements are reformed using UD decomposition. In the filtering stage, a fault detection and isolation method for nanosatellite rate gyros is presented based on using the corresponding innovation sequence. The innovations are used to find where and when the gyroscope faults occurred and determine the corresponding scale factor values of the rate gyros of the nanosatellite. In presence of measurement sensor fault, the isolation process finds on which axis of the rate gyro failure occurred.